Supporting group coherence in a museum visit - Fosh, Lesley; Benford, Steve; Koleva, Boriana (2016)
Visiting museums as part of a group poses the challenge of managing engagement with exhibits while preserving group cohesion. We respond to this by reconfiguring the social dynamic of visiting with an experience designed specifically for groups, that invites the group members themselves to design and ‘gift’ interpretations to one another. We present a trial of this experience with groups of family and friends at a museum. We show how groups managed and configured themselves during the visit, revealing the strategies involved in maintaining different group behaviors. We discuss how our design accommodated different visiting styles by making objects social and scaffolding rather than directing the group experience. We interpret our findings to frame group coherence as a flexible and configurable phenomenon within CSCW.